2018
DOI: 10.1088/1748-605x/aa91d9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein-coated nanofibers on conformation of gingival fibroblast spheroids: potential utility for connective tissue regeneration

Abstract: Deep wounds in the gingiva caused by trauma or surgery require a rapid and robust healing of connective tissues. We propose utilizing gas-brushed nanofibers coated with collagen and fibrin for that purpose. Our hypotheses are that protein-coated nanofibers will: (i) attract and mobilize cells in various spatial orientations, and (ii) regulate the expression levels of specific extracellular matrix (ECM)-associated proteins, determining the initial conformational nature of dense and soft connective tissues. Ging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 63 publications
(96 reference statements)
1
12
0
Order By: Relevance
“…PLGA nanofibers coated with fibrin, collagen or no protein were placed on top of fibroblast spheroids for gingiva connective tissue engineering. (104) Fibers with collagen and fibrin prompted cell extensions protruding out of the spheroid, while uncoated fibers induced no spheroid migration. Further experiments showed collagen coated nanofibers allowed fibroblasts to migrate deeper into the scaffold and fuse into larger microtissues.…”
Section: Biomaterials To Influence Spheroid Functionmentioning
confidence: 98%
“…PLGA nanofibers coated with fibrin, collagen or no protein were placed on top of fibroblast spheroids for gingiva connective tissue engineering. (104) Fibers with collagen and fibrin prompted cell extensions protruding out of the spheroid, while uncoated fibers induced no spheroid migration. Further experiments showed collagen coated nanofibers allowed fibroblasts to migrate deeper into the scaffold and fuse into larger microtissues.…”
Section: Biomaterials To Influence Spheroid Functionmentioning
confidence: 98%
“…However, Kaufman et al (2018) seeded fibroblast monolayers and 3D spheroids on poly‐(DL‐lactide‐co‐glycolide; PLGA) nanofibres coated with collagen. The authors showed that the collagen‐coated scaffolds induced higher levels of cell migration towards fibres and supported cellular growth within them.…”
Section: Discussionmentioning
confidence: 99%
“…The biomaterial also induced higher gene expression values of key components of the extracellular matrix (ECM; type I collagen, FN and MMP2) than uncoated scaffolds. Therefore, collagen-coated scaffolds have a strong potential for use in connective tissue engineering applications, as they have the structural characteristics and functions required for wound healing applications (Kaufman et al, 2018). In another study, different formulations of 3D electrospun PLGA scaffolds, either modified with collagen-I and/or FN or not, were developed to assess the synergistic effects of these proteins on supporting the viability and functional properties of Huh-7.5 cells (Das et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…14 At the same time, the cells also release the catabolic ingredients, including MMPs, to make the constituting periodontal tissue balanced. 15 During the inflammation, however, the fibroblasts are also involved in part of the disease progression. Studies have shown that the bacteria themselves or the bacterial products, such as lipopolysaccharide (LPS), could induce the expression or release of certain inflammatory mediators from the gingival or periodontal fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…These fibroblasts produce and secret the metabolic substances, such as the collagen, in structuring the gingival and periodontal extracellular matrix 14 . At the same time, the cells also release the catabolic ingredients, including MMPs, to make the constituting periodontal tissue balanced 15 . During the inflammation, however, the fibroblasts are also involved in part of the disease progression.…”
Section: Introductionmentioning
confidence: 99%